FEATURES OF THE ISO 14040/14044 LIFE CYCLE ASSESSMENT METHODOLOGY AND ITS INDUSTRY-BASED ADAPTATION IN LIGHT INDUSTRY - IVANISHENA, TETIANA; NADOPTA, TETIANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article examines the methodological foundations of Life Cycle Assessment (LCA) according to ISO 14040 and ISO 14044 and substantiates their industry-specific adaptation for the light industry, particularly textile, clothing and footwear production. The study highlights the importance of full-cycle environmental evaluation as a key instrument for sustainable product development and strategic environmental management. Special attention is paid to methodological challenges arising from complex supply chains, high material and energy consumption, chemical-intensive processes, and data uncertainty typical for textile manufacturing. The paper systematizes the four classical LCA stages—goal and scope definition, inventory analysis, impact assessment, and interpretation—and analyses their practical implementation under real production conditions. It emphasizes critical issues such as functional unit selection, system boundary definition, acquisition of primary data, modeling of chemical processes, and the need for geographically specific indicators for water and toxicity assessment. Considerable focus is placed on the role of the use phase, which may contribute up to 96% of the total environmental impact for some textile products. The study proposes a modified LCA structure tailored for the light industry, integrating additional sector-relevant indicators: water scarcity footprint, chemical load, microplastic release, and durability. It also outlines the importance of sensitivity analysis and uncertainty evaluation to ensure methodological transparency and compliance with ISO requirements. The discussion highlights the necessity of harmonizing ISO-based LCA studies with EU Product Environmental Footprint Category Rules (PEFCR) for apparel and footwear to enhance comparability and prevent methodological variability or green washing. The article concludes that adapted LCA methodology can significantly improve sustainable design, resource optimization, eco-modernization and environmental competitiveness of enterprises in the light industry sector.